Protecting Metals from Corrosion: Preserving Durability and Longevity (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Corrosion poses a significant challenge to the durability and reliability of metal structures, equipment, and infrastructure across industries. Protecting metals from corrosion is crucial to ensure their longevity and operational efficiency. This abstract provides an overview of the importance of corrosion protection and highlights common techniques employed in the field. Protective coatings act as a physical barrier, while galvanic protection methods utilize sacrificial metals or impressed current to shield the primary metal. Appropriate alloy selection enhances corrosion resistance, and corrosion inhibitors form protective films on metal surfaces. Additionally, emerging innovations in nanostructured materials, organic coatings, and smart monitoring systems offer promising avenues for advanced corrosion prevention strategies. By implementing effective corrosion protection measures, industries can mitigate the economic and safety risks associated with corrosion, ensuring the preservation and extended service life of metal assets.